Disparity in Human Rights Violations: A Political and International Law Perspective - Daud, Aidir Amin (Faculty of Law, Hasanuddin University, 2016)
Right to life is non-derogable rights. A natural right that should not be revoked arbitrarily by anyone, including the state. A mass murder in events 1 October 1965 and Timor-Timor is a double series of states’ failure in protecting the rights of Indonesian peoples. Moreover, these two events get different treatment in its handling. The disparity in treatment between two cases is a big question related to the consistency of human rights enforcement in Indonesia. This study is a descriptive-qualitative research. While, to prove the truth, this study will use a comparative study. The findings show that the attitude of the United Nations that treat serious human rights violations in Timor-Timor and the events of 1965 in Indonesia, cannot be answered differently in the perspective of international law. Since it has a weakness where the political interests of ruling is very strong in influencing the decisions of the UN. The disparity in law enforcement in the event of serious human rights violations in 1965 and Timor-Timor due to the dynamics of international politics when it does not allow for the demands of human rights violations to the UNs’ International Court due to advantage for a certain state after the event. In order to reduce disparities in human rights violations, reconciliation is the most rational solution at this time compared remains demand the state for the violations. Besides, many human rights violations in certain countries that have successfully resolved through reconciliation approach.